Progress in Functional Manufacturing Technologies III Special topic volume with invited peer reviewed papers only. (Trans Tech Publications Ltd, 2013)
Volume is indexed by Thomson Reuters BCI (WoS).The special volume communicates the latest progress and research results of new theory, new technology, method, equipment and so on in advanced manufacturing technology field, and to grasp the updated technological and research trends internationally. The major topics covered by the special volumes include Applied Materials Engineering, Materials Processing Technologies and Mechanical Engineering, Monitoring Method and Technology in Mechanical Engineering, Control System in Mechanical Engineering, Management and Development of Manufacturing Technologies. In invited and peer reviewed reports, researchers share their methods and findings in applied materials engineering, materials processing technologies, and mechanical engineering; monitoring methods and technology in mechanical engineering; control systems in mechanical engineering, and managing and developing manufacturing technologies. The topics include the concept of controlled speed based on a cutting band saw, the experimental investigation of electroformed copper-based zirconia nanocomposites aided by ultrasound, a chaos time series on chatter signal recognition, an expert decision system for spraying trellis crops, and investigating a spinning process module by a textile collaborative design system.